An analysis of factors affecting households’ participation in land consolidation in Rwanda - Joseph Ndagijimana; Aristide Maniriho; Liberata Mukamana (Cogent Social Sciences, 2025)
This study uses cross-sectional survey data collected countrywide by the National Institute of Statistics of Rwanda (EICV 5) from a random sample of 14,580 households. This study significantly contributes to understanding the drivers of land consolidation in Rwanda by revealing that socioeconomic factors, institutional frameworks, and location variables critically influence household participation, which remains limited despite its agricultural reform importance, thereby informing targeted policy interventions. We used Multinomial Logistic Regression Model to evaluate household responses across all 30 districts in Rwanda. For an appropriate analysis, we exploited the odds ratio of logistic regression and marginal effects by setting the theoretical framework and mode for each variable characteristic. The study found that one out of five households is engaged in land consolidation, highlighting its limited adoption despite its significance in the country’s agricultural reforms. Furthermore, socioeconomic and institutional factors and location had a significant impact on households’ participation in land consolidation. Additionally, factors such as household size, livestock ownership and agricultural input use, including fertilizer, irrigation, and improved seeds showed strong positive and statistically significant effects on land consolidation participation. Accordingly, policy-makers should prioritize locations with existing irrigation infrastructure and large areas of consolidated land.